The way of the nomad: Daily life of Atlixco through the photograph of Ralph H. Cake - Vázquez Valdés, Verónica; Deance Bravo y Troncoso, Iván Gerardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this work we present the process of ordering, cataloging and curating the photographic materials of an American anthropologist who carried out fieldwork in Atlixco, Puebla, Mexico, with indigenous people of the Nahua ethnic group in the 1970s and 1980s. The methodology used for this work was based on an own proposal of minimum cataloging of photographic materials. We conclude that minimal cataloging is suitable for interoperability with international standards and is easy to apply in university and local archive contexts.